Dip moveout processing - Hale, Dave, 1955- (Society of Exploration Geophysicists, 1991)
This volume assists geophysicists in both implementing and evaluating DMO processing. It discusses the theory, motives, and limitations underlying the most popular DMO methods.
"An SEG continuing education short course."
Keywords: Seismology -- Mathematics.; Fourier transformations.; elektronické knihy; electronic books